2011
DOI: 10.1097/bpb.0b013e328347c2bc
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intraoperative supine and postoperative standing radiographs after posterior instrumentation for adolescent idiopathic scoliosis

Abstract: The utility of intraoperative radiographs after posterior spinal segmental instrumentation for adolescent idiopathic scoliosis (AIS) is debatable. A retrospective review of 74 patients with moderately severe AIS revealed the main thoracic Cobb measurements of 57° preoperatively, 17° intraoperatively, 18° on initial postoperative, and 20° on final postoperative radiographs. On the basis of the extent and type of instrumentation (pedicle screws vs. hybrid construct), there was no clinically significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Given that most surgeons verify the deformity correction using intraoperative radiographs, it is crucial to elucidate risk factors for postoperative complications using these radiographs. According to previous studies, frontal plane correction measured using intraoperative supine radiographs is comparable with similar measurements made using the full-length postoperative standing radiographs 17 . Lehman et al 18 have reported that intraoperative prone long-cassette scoliosis film correlated with the immediate postoperative standing film for all curve correction and balance parameters.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Given that most surgeons verify the deformity correction using intraoperative radiographs, it is crucial to elucidate risk factors for postoperative complications using these radiographs. According to previous studies, frontal plane correction measured using intraoperative supine radiographs is comparable with similar measurements made using the full-length postoperative standing radiographs 17 . Lehman et al 18 have reported that intraoperative prone long-cassette scoliosis film correlated with the immediate postoperative standing film for all curve correction and balance parameters.…”
Section: Discussionmentioning
confidence: 55%
“…According to previous studies, frontal plane correction measured using intraoperative supine radiographs is comparable with similar measurements made using the fulllength postoperative standing radiographs. 17 Lehman et al 18 have reported that intraoperative prone long-cassette scoliosis film correlated with the immediate postoperative standing film for all curve correction and balance parameters. Therefore, intraoperative radiographs are a valuable tool regardless of the patient's position when taken.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the inclusion and exclusion criteria, and quality assessment, 24 case-control studies with a total of 3042 AIS patients (1582 PS, 1460 HI) were finally included. [6,1719,2140] One RCT, 1 prospective study, and 22 retrospective studies were included. The flow diagram of study selection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[17] In Lonner's article, the subgroup data of monoaxial and polyaxial pedicle screw groups were combined into PS group. [18] In Fu's study, the subgroup data of hook and wire groups were combined into HI group.…”
Section: Methodsmentioning
confidence: 99%